Correction: The intersection of finTech adoption, HR competency potential, service innovation, and firm growth in the banking sectors using Entropy and TOPSIS. - Habib Ullah Khan; Muhammad Abbas; Shah Nazir; Faheem Khan; Yeon-Kug Moon (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0313210.].